Economic security in the digital economy in Vietnam - Do Thi Kim Tien (Journal of State Management, 2025)
Ensuring socio-economic stability and development has always been a critical concern for nations throughout history, directly influenced by economic security. In the current context, the rapid advancement of the technological revolution, accompanied by digital transformation and the growth of the digital economy, has presented numerous opportunities while also posing significant challenges to Vietnam’s economic security. This study aims to clarify the nature of economic security and identify the risks and challenges posed by the digital economy. Based on these insights, it proposes strategic directions and policy solutions to overcome such challenges, effectively adapt to the new context, and fully leverage development opportunities in the country’s digital era.